STUDI ANALISIS KONSISTENSI DAN KECUKUPAN BAHAN AJAR MATERI DEMOKRASI PADA DIKTAT PENDIDIKAN KEWARGANEGARAAN KELAS X TUNARUNGU DI SLB NEGERI SURAKARTA TAHUN AJARAN 2016/2017 - Hanik, Camelia; Suryono, Hassan; ., Wijianto (PKn Progresif, 2017)
ABSTRACTThis research aimed to: (1) improve the accuracy of consistency principle of materials for the topic of Democracy within the Dictate of Civic Education for class X of hearing impaired students, (2) improve the accuracy of sufficiency principle of materials for the topic of Democracy within the Dictate of Civic Education in class X of hearing impaired students.This research used embedded single qualitative method. Data were collected by means of interview, document analysis, and observation. Triangulation of data and theories were conducted to ensure the data validity. The data were then analyzed using content analysis method.Based on the research findings, it was concluded that: (1) Dra.Wahyu Trimei Pujilestari?s Dictate of Civic Education for class X of hearing impaired students had not fully met the consistency principle and the determined indicators in the syllabus. This was evident from the fact that there were still some indicators of consistency principle that were not covered yet, such as: a. balance of the materials, b. range of the materials, and c. presentation of the materials; (2) Materials for the topic of Democracy within the Dictate of Civic Education in class X of hearing impaired students had not met the sufficiency principle, of which materials to be taught should be adequate to help students master basic competences. This was proved by the fact that there were several indicators of sufficiency principle that had not been covered such as: a. coverage of the materials, b. connection with Pancasila, c. accuracy of the facts. Materials in the syllabus were not fully listed in the Dictate of Civic Education in class X of hearing impaired students. Some addition and omission were necessary. Keywords : Consistency, Sufficiency, Teaching Materials, Dictate